Digital Religious Literature and Its Role in Shaping Religious Moderation among Indonesian University Students - Amirudin; Suyono; Soeprijanto; M. Hudri (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
Digital religious literature circulating on social media has reshaped how university students access and interpret Islamic teachings, yet limited research has examined how the narrative structure of these digital texts influences the formation of religious moderation. This study addresses this gap by analysing how digital interpretations of QS. Al Hujurat 49:13 construct specific emphases of meaning and how students internalise these messages. The research employs a descriptive qualitative design using two types of data: digital religious texts from tafsir applications, YouTube, and Instagram, and interview data from university students. These data were analysed through content analysis and hermeneutic interpretation to identify narrative patterns, framing strategies, and interpretive tendencies. The findings show three key patterns. First, digital interpretations consistently highlight equality, diversity, and social harmony, producing simplified moral messages that are easily circulated. Second, the structure of digital texts compresses and fragments Quranic meaning, reducing engagement with socio historical context and limiting interpretive plurality. Third, students’ levels of digital literacy significantly shape how they evaluate and internalise moderation narratives, functioning as an epistemic filter that distinguishes reflective understanding from superficial acceptance. These findings indicate that digital platforms do not merely transmit religious messages but actively shape interpretive outcomes through narrative design and algorithmic visibility. The study contributes to digital religion scholarship by demonstrating that religious moderation in the digital era is a mediated interpretive product. It recommends strengthening critical digital literacy and improving the contextual quality of digital religious content to support deeper and more balanced interpretations among students.